Complementarities and network externalities in casually copied goods - Blackburn, David (Estudios de Economía, 2016)
In this paper, we examine the impacts of casual copying in the market for goods that have strong network externalities and/or are strong complements with goods in another market. By allowing casual copying to occur, the monopolist triggers two effects. The ""copying effect"" reduces demand (and thus profits) due the introduction of a better outside alternative to consumers. However, a ""network augmenting"" effect works to increase demand through the larger size of a network that allows copying. We find that if the marginal network externality is large enough, the monopolist will find it profitable to allow some level of casual copying to occur among non-purchasers of the good. And in a simplified dynamic setting, we find that as time passes and the good’s network becomes more mature, the monopolist will seek higher and higher levels of copy protection. This implies that firms in newly formed markets should be more willing to allow copying to occur than those in established markets. "